Component processes subserving rapid automatized naming in dyslexic and non-dyslexic readers - Araújo, Susana (2014)
The current study investigated which time components of rapid automatized naming (RAN) predict group differences between dyslexic and non-dyslexic readers (matched for age and reading level), and how these components relate to different reading measures. Subjects performed two RAN tasks (letters and objects), and data were analyzed through a response time analysis. Our results demonstrated that impaired RAN performance in dyslexic readers mainly stem from enhanced inter-item pause times and not from difficulties at the level of post-access motor production (expressed as articulation rates). Moreover, inter-item pause times account for a significant proportion of variance in reading ability in addition to the effect of phonological awareness in the dyslexic group. This suggests that non-phonological factors may lie at the root of the association between RAN inter-item pauses and reading ability. In normal readers, RAN performance was associated with reading ability only at early ages (i.e. in the reading-matched controls), and again it was the RAN inter-item pause times that explain the association.